2006
DOI: 10.1097/01.mlr.0000215806.11805.6c
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Adherence to Guidelines for Antipsychotic Dose and Health Status, Side Effects, and Patient Care Experiences

Abstract: There was no evidence that health status was better on higher-than-recommended doses, but we cannot conclude that lower doses for some would have led to poorer outcomes. Physicians who believe that higher doses are more therapeutic for patients need to demand rigorous effectiveness research that tests whether there are benefits of higher doses and determine the ratio of those benefits to the clinical costs, including the risk of side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…The benefit of increasing doses is uncertain; for example, studies that have compared doses higher than 2000 mg of chlorpromazine per day with lower doses have demonstrated superior efficacy for high-dose treatment (Quitkin, Rifkin, & Klein, 1975;Ericksen et al, 1978;McCreadie & MacDonald, 1977) while high doses of haloperidol have not proved to be more effective (Van Putten et al, 1992). Dickey et al (2006) examined the relationship between evidencebased antipsychotic medication dose and health status, perceptions of care, and medication side effects among the acutely ill, high-risk patients with schizophrenia. They found that higher than recommended doses were not related to better outcomes.…”
Section: Dosing In Schizophreniamentioning
confidence: 99%
“…The benefit of increasing doses is uncertain; for example, studies that have compared doses higher than 2000 mg of chlorpromazine per day with lower doses have demonstrated superior efficacy for high-dose treatment (Quitkin, Rifkin, & Klein, 1975;Ericksen et al, 1978;McCreadie & MacDonald, 1977) while high doses of haloperidol have not proved to be more effective (Van Putten et al, 1992). Dickey et al (2006) examined the relationship between evidencebased antipsychotic medication dose and health status, perceptions of care, and medication side effects among the acutely ill, high-risk patients with schizophrenia. They found that higher than recommended doses were not related to better outcomes.…”
Section: Dosing In Schizophreniamentioning
confidence: 99%
“…In a previous Medicaid database study, Dickey et al (Dickey et al, 2006) found adherence to the 1998 Schizophrenia PORT antipsychotic dosage recommendations were generally unrelated to measures of health status. Physical health was better, but not significantly, in the group whose dose was within the guideline recommendations.…”
Section: Discussionmentioning
confidence: 97%
“…In this study schizophrenia-specific positive or negative symptoms related to adherence to specific medications were not measured, mainly because the authors think that patients treated in clinical settings are more diverse than those in clinical trials (Dickey et al 2006). Instead outcomes measures that reflected more general benefits of problem reduction and community functioning such as the rates of patients' physical restraint, in hospital re-admission and job re-insert were used.…”
Section: Discussionmentioning
confidence: 98%
“…According to other studies doctors and nurses experience difficulties in including evidence-based practices within the care pathway, mainly because of divergent views on the nature of standardized care for people with schizophrenia (Jones 2004;Dickey et al 2006). However, this did not affect the care pathway implementation and the results of the study showed significant improvements of the quality of the process of care when compared to the traditional one.…”
Section: Discussionmentioning
confidence: 99%